Dermoid cyst with secretion of CA 19-9 detected by 18F-FDG PET/CT: A case report. Issue 10 (March 2020) - Lin, Sheng-Che; Yen, Ruoh-Fang; Chen, Yen-Kung
Abstract: Introduction: Carbohydrate antigen 19-9 (CA 19-9) is a tumor glycolipid, frequently elevated in the serum of patients due to malignancies from gastrointestinal organs; in particular, the pancreas. This carbohydrate antigen is also expressed in benign diseases. Patient concerns: A case of a 27-year-old female who has an unknown origin CA 19-9 elevation for 2 years. Diagnosis: After the left ovarian cystectomy and microscopic examination, the final diagnosis is a dermoid cyst. The dermoid cyst shows increased 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake in the 18 F-FDG positron emission tomography (PET)/computed tomography (CT) study. Intervention and outcomes: The laparoscopic oophorocystectomy was performed. It was observed that the patient's CA 19-9 level returned to normal after the surgery 6 months later. This showed that the dermoid cyst was responsible for the abnormal CA 19-9 level. Conclusion: In this case, we can learn that the 18 F-FDG PET/CT scan has potential use in patients with unknown origin of elevation CA 19-9.